Thermal Unequilibrium of PdSn Intermetallic Nanocatalysts: From In Situ Tailored Synthesis to Unexpected Hydrogenation Selectivity. Issue 33 (16th July 2021) - Chen, Minda; Yan, Yu; Gebre, Mebatsion; Ordonez, Claudio; Liu, Fudong; Qi, Long; Lamkins, Andrew; Jing, Dapeng; Dolge, Kevin; Zhang, Biying; Heintz, Patrick; Shoemaker, Daniel P.; et al.
Abstract: Effective control on chemoselectivity in the catalytic hydrogenation of C=O over C=C bonds is uncommon with Pd‐based catalysts because of the favored adsorption of C=C bonds on Pd surface. Here we report a unique orthorhombic PdSn intermetallic phase with unprecedented chemoselectivity toward C=O hydrogenation. We observed the formation and metastability of this PdSn phase in situ. During a natural cooling process, the PdSn nanoparticles readily revert to the favored Pd3 Sn2 phase. Instead, using a thermal quenching method, we prepared a pure‐phase PdSn nanocatalyst. PdSn shows an >96 % selectivity toward hydrogenating C=O bonds of various α, β‐unsaturated aldehydes, highest in reported Pd‐based catalysts. Further study suggests that efficient quenching prevents the reversion from PdSn‐ to Pd3 Sn2 ‐structured surface, the key to the desired catalytic performance. Density functional theory calculations and analysis of reaction kinetics provide an explanation for the observed high selectivity. Abstract : Metastable PdSn intermetallic nanoparticles are made through a rapid quenching method, inspired by in situ characterization results. PdSn shows unprecedented high hydrogenation selectivity of C=O over C=C bonds in α, β‐unsaturated aldehydes.